Application of the Apriori Algorithm in PT XYZ - Neves, Cipriano Bruno das; Ridwan (Green Publisher, 2025)
Competition in the business world, especially in the increasingly difficult printing world, requires developers to find strategies to increase orders for printed products ordered. An increasing number of order data every day can be used to develop marketing strategies if processed correctly. A priori algorithms include the type of association rules in data mining. One of the stages of association analysis that attracts many researchers to produce efficient algorithms is the analysis of high-frequency patterns (frequent pattern mining). The importance of an association can be known by two benchmarks, namely: support and confidence. Support (support value) is the percentage of the combination of these items in the database, while confidence (certainty value) is the strength of the relationship between items in association rules.